Multiple sialolithiasis of submandibular gland: a case report - Nurwahida Nurwahida; Andri Hardianto; Kiki A. Rizki (Journal of Dentomaxillofacial Science, 2017)
Objective: Sialolithiasis is a common disease of the salivary glands. Sialolithiasis occurs mainly in the submandibular gland (80–90%) and to a lesser extent in the parotid gland (5–20%). Sialoliths may be single or multiple. Multiple sialolith in the submandibular gland are rare. Seventy to 80% of cases feature solitary stones; only about 5% of patients have three or more stones. Patients commonly experience pain and/or swelling.Methods: A 51-year-old male came to Department of Oral and Maxillofacial Surgery with a swelling and pain at the right submandibular. The panoramic radiograph showed a radiopacity mass with well-defined in right submandibular. The Ultrasonographic interpretation showed hypoechoic inhomogeneous mass with multiple calcification.The submandibular gland removal was performed by extraoral approach.Result:Multiple sialolith in the submandibular gland are rare. A surgical approach for removal of sialolith in the submandibular gland could be intraoral or extraoral. In this case report, we described five stones in the submandibular gland. which were removed by extraoral approach.Conclusion: There are various methods available for the management of salivary stones. In this case report, removal of the submandibular gland with the stone should still be preferred as the gold standard of treatment and could avoid recurrence of this medical condition.